Kontribusi Fisiologi Olahraga Mengatasi Resiko Menuju Prestasi Optimal - HB., Bafirman (Universitas Negeri Semarang, 2013)
Optimal achievement in sports can be achieved if training quality is to be applied, and embracing the concept of coaching pyramid as the process of achieving goals. Use of science and technology to obtain information about the physiological characteristics of athletes, to serve as guidelines in making the exercise program. Management application of the load must be carried out with due regard to the physiological condition of each athlete, and the application of the burden in training need to stimulate the physiological capabilities of the athlete. Error in applying the load of management practice, will have a negative impact on the physiological condition of the athlete. The pulse rate is high, often feel dizzy, disturbances in digestion and metabolism, an effect caused by overtraining, affect the performance athletes to achieve optimal performance. Overtraining condition occurs due to errors in applying the training program.